2018
DOI: 10.1038/s41391-018-0040-2
|View full text |Cite
|
Sign up to set email alerts
|

Does the association of prostate cancer with night-shift work differ according to rotating vs. fixed schedule? A systematic review and meta-analysis

Abstract: This is the first meta-analysis suggesting that an increased risk of prostate cancer may be restricted to workers with rotating night shifts. However, the association was weak and additional studies are needed to further clarify this relation before it can be translated into measures for risk reduction in occupational settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 36 publications
5
34
1
6
Order By: Relevance
“…Our dose-response analysis demonstrated that every extra year of shift work is causing a significant increase of 2% of melanoma. Similar results were demonstrated in several studies that showed higher risks of colorectal, breast, lung and prostate cancers with an increased duration of shift work [26][27][28][29][30][31][32] . The results presented herein, together with the findings of the previously mentioned studies, suggest that longer exposure to shift work increases the risks of different types of cancers.…”
Section: Discussionsupporting
confidence: 89%
“…Our dose-response analysis demonstrated that every extra year of shift work is causing a significant increase of 2% of melanoma. Similar results were demonstrated in several studies that showed higher risks of colorectal, breast, lung and prostate cancers with an increased duration of shift work [26][27][28][29][30][31][32] . The results presented herein, together with the findings of the previously mentioned studies, suggest that longer exposure to shift work increases the risks of different types of cancers.…”
Section: Discussionsupporting
confidence: 89%
“…Among those articles, 41 (85%) used shift work as the exposure, and 12 (25%) used long work hours. The articles covered the following outcomes: cancers [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] (16, 33%), cardiovascular disease [33][34][35][36][37][38][39][40][41] (9, 19%), metabolic syndrome, diabetes mellitus, and obesity [42][43][44][45][46][47][48][49][50] (9, 19%), complications of pregnancy [51][52][53][54][55][56][57][58] (8, 17%), depression [43,45,59] (4, 8%), hypertension [60] (1, 2%), and injuries [61] (1, 2%). Some conditions we identified to be chronic or high cost (e.g.…”
Section: Overview Of Search Resultsmentioning
confidence: 99%
“…However, summary measurements must be considered with caution, due to the high heterogeneity found, the high proportion of studies with low-medium methodological quality, and the possibility of publication bias. As we have previously mentioned, other authors have also tried to summarize available evidence [27][28][29][30][31][32][33], as shown in online Supplementary Table S1.…”
Section: Discussionmentioning
confidence: 99%
“…From an epidemiological perspective, a number of observational studies have tried to evaluate the association between shift work and prostate cancer, although their results do not always point in the same direction [25,26]. This has led to the conduction of several reviews and meta-analyses on this topic, albeit again with inconsistent results [27][28][29][30][31][32][33]. A detailed analysis reveals that they have significant methodological weaknesses, such as high unexplained heterogeneity [28], partial inclusion of the evidence due to restrictions based on study design [27] or type of exposure (i.e., restricted to permanent night jobs), or the absence of consideration of potential publication bias [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation